THE EFFECT OF USING SHORT SILENT ANIMATIONS ON EFL LEARNERS’ WRITING - Hamid Marashi; Hedieh Adiban (University of Kuningan, 2017)
This study investigated the effect of short silent animations on pre-intermediate EFL learners’ writing. A homogenized group of 60 participants was non-randomly chosen and assigned as the control and experimental groups. Those in the control group watched five short animations with dialogue, while those in the experimental group had five short animations which were silent. The procedure lasted 10 sessions. In both groups, the participants were asked to write five writings regarding the subjects of the animations during the term and each of the writings should have contained a minimum of 90 and maximum of 140 words. The participants were provided both oral and written feedback. At the end of the instruction, a sample PET writing posttest was administered to both groups, an independent samples t-test was run on the mean scores of the two groups, and the results (t = -2.02, p = 0.0370.05) revealed that the experimental group outperformed the control group. Keywords: ELT, silent animations, writing